Project Assignments Assessment in the Content-Integrated Language Course: Stages, Forms, and Online Tools - S. V. Titova (Высшее образование в России)
Today, according to various educational documents, a university teacher must be able to control the learning process not only in order to compare the level achieved by students with a certain minimum of requirements laid down in the curriculum on the basis of competent and transparent assessment criteria and to record changes in the general level of preparedness of each student and the dynamics of his successes, but for the diagnosis of problems that arise among students in the learning process (formative assessment); for the development of reflection skills; skills of self-assessment and peer-assessment by students of their achievements. Unfortunately, at the current stage, peer-assessment, reflection and self-assessment are a weak point in the educational process, since usually the student does not participate in control and assessment, he is not involved in the process of developing or choosing assessment criteria, in peer and self-assessment, in reflective activity after completing the project assignment or taking a course. The article examines control and feedback as important components of the methodological system: the stages of control, assessment methods, control and reflection tools. The purpose of this article is to develop the approaches for assessing professionally oriented projects within the framework of a content-integrated language course (CLIL). The article analyzes the didactic potential of feedback during project activities and the conditions for providing effective feedback. The stages of web projects’ assessment, the pre requisites for the successful implementation of the activity in blended learning are described as well as online tools and mobile applications that allow to ensure effective feedback, reflection and assessment in a content-integrated language course.